Dolutegravir dosing for children with HIV weighing less than 20 kg: pharmacokinetic and safety substudies nested in the open-label, multicentre, randomised, non-inferiority ODYSSEY trial. Issue 5 (May 2022) - Waalewijn, Hylke; Chan, Man K; Bollen, Pauline D J; Mujuru, Hilda A; Makumbi, Shafic; Kekitiinwa, Adeodata R; Kaudha, Elizabeth; Sarfati, Tatiana; Musoro, Godfrey; Nanduudu, Annet; Lugemwa, Abbas; Amuge, Pauline; et al.
Summary: Background: Dolutegravir-based antiretroviral therapy is a preferred first-line treatment for adults and children living with HIV; however, very little pharmacokinetic data for dolutegravir use are available in young children. We therefore aimed to evaluate dolutegravir dosing and safety in children weighing 3 kg to less than 20 kg by assessing pharmacokinetic parameters and safety data in children taking dolutegravir within the ODYSSEY trial. Methods: We did pharmacokinetic substudies nested within the open-label, multicentre, randomised, non-inferiority ODYSSEY trial. We enrolled children from seven research centres in South Africa, Uganda, and Zimbabwe. Children weighing 3 kg to less than 14 kg received 5 mg dispersible tablets of dolutegravir according to WHO weight bands: 5 mg for children weighing 3 kg to less than 6 kg and younger than 6 months, 10 mg for children weighing 3 kg to less than 6 kg and aged 6 months or older, 15 mg for children weighing 6 kg to less than 10 kg, and 20 mg for children weighing 10 kg to less than 14 kg. Children weighing 14 kg to less than 20 kg received a 25 mg film-coated tablet once per day early in the trial or 25 mg dispersible tablets (five 5 mg tablets once per day) later in the trial. A minimum of eight children per weight band or dose was targeted for 24 h pharmacokinetic profiling at steady state. The primary pharmacokinetic parameter was the trough concentration 24 h after observed dolutegravir intake (Ctrough ). Pharmacokinetic targets were based on adult dolutegravir Ctrough and the 90% effective concentration (EC90 ; ie, 0·32 mg/L). Safety was evaluated in eligible children consenting to pharmacokinetic substudies. Findings: Between May 25, 2017, and Aug 15, 2019, we enrolled 72 children aged between 3 months and 11 years. 71 children were included in the safety population and 55 (76%) of 72 children contributed 65 evaluable pharmacokinetic profiles. Geometric mean Ctrough in children on dispersible tablets in weight bands between 3 kg and less than 20 kg ranged between 0·53–0·87 mg/L, comparable to the adult geometric mean Ctrough of 0·83 mg/L. Variability was high with coefficient of variation percentages ranging between 50% and 150% compared with 26% in adults. Ctrough below EC90 was observed in four (31%) of 13 children weighing 6 kg to less than 10 kg taking 15 mg dispersible tablets, and four (21%) of 19 weighing 14 kg to less than 20 kg taking 25 mg film-coated tablets. The lowest geometric mean Ctrough of 0·44 mg/L was observed in children weighing 14 kg to less than 20 kg on 25 mg film-coated tablets. Exposures were 1·7–2·0 times higher on 25 mg dispersible tablets versus 25 mg film-coated tablets. 19 (27%) of 71 children had 29 reportable grade 3 or higher adverse events (13 serious adverse events, including two deaths), none of which were related to dolutegravir. Interpretation: Weight-band dosing of paediatric dolutegravir dispersible tablets provides appropriate drug exposure in most children weighing 3 kg to less than 20 kg, with no safety signal. 25 mg film-coated tablets did not achieve pharmacokinetic parameters in children weighing 14 kg to less than 20 kg, which were comparable to adults, suggesting dosing with dispersible tablets is preferable or a higher film-coated tablet dose is required. Funding: Paediatric European Network for Treatment of AIDS Foundation, ViiV Healthcare, and UK Medical Research Council.